2021
DOI: 10.3389/fnut.2021.717473
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Vitamin D Supplementation and Physiotherapy on Reducing Pain Among Adult Patients With Musculoskeletal Disorders: A Quasi-Experimental Clinical Trial

Abstract: Background: The prevalence of musculoskeletal disorders (MSD) and vitamin D insufficiency is high. Past research indicating vitamin D supplementation and physiotherapy are useful for the treatment of MSDs. However, to the best of our knowledge, the combined benefits of vitamin D and physiotherapy are not yet evaluated in MSD. We hypothesized that combined intervention of vitamin D supplementation and physiotherapy would be more effective in relieving the pain of MSD compared to only physiotherapy intervention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
(47 reference statements)
1
23
0
Order By: Relevance
“…The Global Burden of Disease Study 2019 found MHC the leading cause of disability that affected 1.7 billion people worldwide. 4 , 5 Subsequently, since the pandemic started in 2019, more than 0.56 billion of the world population have been infected by SARS-CoV-2, and the number is increasing every day. 6 To make the situation worse, scientists predicted the incidence of MHC would be raised in the post-pandemic era in 3 specific ways.…”
Section: Introductionmentioning
confidence: 99%
“…The Global Burden of Disease Study 2019 found MHC the leading cause of disability that affected 1.7 billion people worldwide. 4 , 5 Subsequently, since the pandemic started in 2019, more than 0.56 billion of the world population have been infected by SARS-CoV-2, and the number is increasing every day. 6 To make the situation worse, scientists predicted the incidence of MHC would be raised in the post-pandemic era in 3 specific ways.…”
Section: Introductionmentioning
confidence: 99%
“…The full texts of the 27 remaining studies were read, and their content was cross-referenced with the inclusion criteria. A total of 14 studies met the eligible criteria [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Details regarding the included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A treatment with a vitamin D supplement and a standard antidepressant prescribed to FMS patients with 25OHD deficiency could lead to significant benefits in terms of both physical and psychological symptoms [ 36 ]. The combined benefit of vitamin D supplementation and physiotherapy was significantly higher than physiotherapy alone in improving pain-related symptoms (−4.92 vs. −3.79; p < 0.001) in CMP patients [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations